Introduction to digital pathology and computer-aided pathology - Soojeong Nam; Yosep Chong; Chan Kwon Jung; Tae-Yeong Kwak; Ji Youl Lee; Jihwan Park; Mi Jung Rho; Heounjeong Go (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Digital pathology (DP) is no longer an unfamiliar term for pathologists, but it is still difficult for many pathologists to understand the engineering and mathematics concepts involved in DP. Computer-aided pathology (CAP) aids pathologists in diagnosis. However, some consider CAP a threat to the existence of pathologists and are skeptical of its clinical utility. Implementation of DP is very burdensome for pathologists because technical factors, impact on workflow, and information technology infrastructure must be considered. In this paper, various terms related to DP and computer-aided pathologic diagnosis are defined, current applications of DP are discussed, and various issues related to implementation of DP are outlined. The development of computer-aided pathologic diagnostic tools and their limitations are also discussed.